2018
DOI: 10.1136/heartjnl-2017-312324
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular adipose tissue and coronary atherosclerosis

Abstract: Adipose tissue (AT) is no longer viewed as a passive, energy-storing depot, and a growing body of evidence supports the concept that both quantitative and qualitative aspects of AT are critical in determining an individual's cardiometabolic risk profile. Among all AT sites, perivascular AT (PVAT) has emerged as a depot with a distinctive biological significance in cardiovascular disease given its close anatomical proximity to the vasculature. Recent studies have suggested the presence of complex, bidirectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
112
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 50 publications
0
112
0
3
Order By: Relevance
“…Both demands are achieved by the systemic sympathetic control and paracrine vasoactive factors released by the cells of the arterial wall. It has been shown that not only endothelial cells but also adipocytes from PVAT, as well as inflammatory cells, play an essential role in maintaining vascular tone and structure [6,12,[16][17][18][19]. In healthy adipose tissue, including PVAT, alternatively activated macrophages M2 prevail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both demands are achieved by the systemic sympathetic control and paracrine vasoactive factors released by the cells of the arterial wall. It has been shown that not only endothelial cells but also adipocytes from PVAT, as well as inflammatory cells, play an essential role in maintaining vascular tone and structure [6,12,[16][17][18][19]. In healthy adipose tissue, including PVAT, alternatively activated macrophages M2 prevail.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, the tunica intima and, partly, the tunica media were the focus of research, and perivascular adipose tissue (PVAT) that surrounds coronary arteries (CAs) was considered to be passive and only supportive tissue. Now, it has become evident that PVAT has a crucial role in maintaining the normal function of CAs [4][5][6], and that it is also involved in the development of CAD [7,8] and hypertension [9]. It has been shown that both vascular smooth muscle and PVAT release a variety of vasoactive factors as well as pro and antiinflammatory cytokines that modulate vascular function and structure [8,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, most investigators systemically removed PVAT from blood vessels before performing biochemical testing, immunostaining, or functional studies as PVAT was considered to be an inert, non-vascular tissue [15]. More recent evidence suggests that communication between the vascular wall and PVAT may be bidirectional, with an 'outside to inside' inflammatory signaling triggered by dysfunctional PVAT more influential than previously thought [6,9,16]. For example, in hyperlipidemic atherosclerosis-prone apolipoprotein E (ApoE)-deficient mice, the major site of vascular inflammatory cell accumulation was reported to be the adventitia rather than the intima, and in atherosclerotic human aorta, inflammatory cells were observed to be densely clustered in PVAT at the adventitial margin, suggesting that PVAT has the potential to foster vascular inflammation [8,17].…”
Section: Adventitial Inflammation and The Pro-inflammatory Phenotype mentioning
confidence: 99%
“…9 It has been recently demonstrated that the adipose tissue surrounding the coronary arteries changes in response to inflammation inside the arteries. 21 Interestingly, the SMART trial identified the low PVAT attenuation on CT as associated with an adverse metabolic profile, the correlation being independent of PVAT volume. This fact suggests that fat quality measures might add complementary information to the one provided by PVAT quantity.…”
mentioning
confidence: 99%
“…25 Therefore, early detection of subclinical CAD could be performed in low-risk to intermediate-risk patients via perivascular noninvasive detection of coronary inflammation by FAI. 26 Perivascular FAI could enable the assessment of inflammatory burden and hence the level of coronary plaque vulnerability, identifying subjects at high risk for developing acute coronary events. These observations further highlight the importance of qualitative over quantitative features in the assessment of human PVAT in order to identify vulnerable patients.…”
mentioning
confidence: 99%